Assessment of Sequelae of COVID-19 Nearly 1 Year After Diagnosis - Zhou, Fangyuan; Tao, Meihui; Shang, Luorui; Liu, Yuhan; Pan, Guangtao; Jin, Yan; Wang, Li; Hu, Shaoke; Li, Jinxiao; Zhang, Mengqi; Fu, Yu; Yang, Shenglan (Frontiers in Medicine, 2021)
Background: A previous study has shown that 81% of the COVID-19 patients had mild or moderate symptoms. However, most studies on the sequelae in COVID-19 patients focused on severe cases and the long-term follow-up studies on the health consequences in non-severe cases are limited. The current study aimed to assess the sequelae of COVID-19 in patients nearly 1 year after diagnosis with a particular focus on the recovery of patients with non-severe COVID-19. Methods: We enrolled 120 patients infected with SARS-CoV-2 discharged from Wuhan Union hospital west district and Fangcang shelter hospitals between January 29, 2020 and April 1, 2020. All participants were asked to complete questionnaires to assess their symptoms and quality of life and for psychological evaluation. Pulmonary function test, chest CT, 6-min walking test (6MWT), routine blood test, liver and kidney function tests, fasting blood glucose test, lipid test, and immunoglobulin G antibody test were performed to evaluate their health. Results: The mean age of the study population was 51.6 ± 10.8 years. Of the 120 patients, 104 (86.7%) were cases of non-severe COVID-19. The follow-up study was performed between November 23, 2020 and January 11, 2021, and the median time between the diagnosis and the follow-up was 314.5 (IQR, 296-338) days. Sleep difficulties, shortness of breath, fatigue, and joint pain were common symptoms observed during follow-up and nearly one-third of the non-severe cases had these symptoms. A total of 50 (41.7%) and 45 (37.5%) patients reported anxiety and depression, respectively. Pulmonary diffusion impairment was reported in 30 (26.1%) out of 115 patients, and 24 (24.2%) out of the 99 non-severe cases. Furthermore, there was a correlation between all the SF-36-domain scores and the duration of hospitalization, pulmonary function, and a 6MWT. Conclusions: At the nearly 1-year follow-up, COVID-19 survivors still had multi-system issues, including those in the respiratory functioning, radiography, quality of life, and anxiety and depression. Moreover, non-severe cases also showed some sequelae and the proportion of IgG negative cases in the non-severe patients was higher than that in severe cases. Therefore, conducting follow-ups and preventing the reinfection of SARS-CoV-2 in this group is necessary.